2021
DOI: 10.1039/d0sm02116d
|View full text |Cite
|
Sign up to set email alerts
|

Near-surface rheology and hydrodynamic boundary condition of semi-dilute polymer solutions

Abstract: Understanding confined flows of complex fluids requires simultaneous access to the mechanical behaviour of the liquid and the boundary condition at the interfaces. Here, we use evanescent wave microscopy to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Moreover, the solvent‐diffusion induced increase of local concentration might create a boundary layer of polymers with concentrations high enough to be considered semi‐dilute. For such a hydrodynamic situation, the no‐slip condition might not apply any more, as elaborated in recent literature 44 . But again, due to the short contact time of the solution with the membrane inside the gap, this process is likely not relevant, especially given that the observed thickening effect does not depend on the initial feed concentration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the solvent‐diffusion induced increase of local concentration might create a boundary layer of polymers with concentrations high enough to be considered semi‐dilute. For such a hydrodynamic situation, the no‐slip condition might not apply any more, as elaborated in recent literature 44 . But again, due to the short contact time of the solution with the membrane inside the gap, this process is likely not relevant, especially given that the observed thickening effect does not depend on the initial feed concentration.…”
Section: Discussionmentioning
confidence: 98%
“…For such a hydrodynamic situation, the no-slip condition might not apply any more, as elaborated in recent literature. 44 But again, due to the short contact time of the solution with the membrane inside the gap, this process is likely not relevant, especially given that the observed thickening effect does not depend on the initial feed concentration. If the above stated effects were substantial, the effect should be more pronounced for higher feed concentrations that are already close to the semi-dilute regime.…”
Section: Conclusion On the Most Likely Explanation Of The Observed Th...mentioning
confidence: 99%
“…We also derived a model based on Brinkman equations and we were able to find an agreement with the experimental results. In perspective, it would be interesting to look at the role of spatial wetting patterning [66][67][68][69]. We hope that this work will open the possibility of an alternative technique to the recycling of ionic liquids.…”
Section: Discussionmentioning
confidence: 99%
“…20 Returning to the advances in practical applications, Guyard et al recently used TIRM to study the near-interface rheology and hydrodynamic boundary condition of semidilute polymer solutions. 72 They found that the monomer charge played a key role in confined polymer dynamics. In neutral polymer solutions, a chain-sized layer of the polymer was formed at the solid-liquid interface, shifting the no-slip plane above the interface.…”
Section: Progress In Different Applicationsmentioning
confidence: 99%